A multicentre survey of pain management in cancer patients and physicians attending radiotherapy clinics in Shandong Province, China. Issue 11 (November 2019) - Tan, Bingxu; Li, Baosheng; An, Yongheng; Ma, Xuezhen; Jiang, Yuhua; Song, Yipeng; Ge, Xingping; Yuan, Shengli; Liu, Liping; Dou, Yan; Yu, Yanxia; Ji, Pu; et al.
Objective: To obtain a better understanding of the prevalence and management of pain in patients undergoing radiotherapy for cancer in Shandong Province, China. Methods: This cross-sectional study used a questionnaire during face-to-face interviews to collect data from physicians and patients regarding the recognition, prevalence and treatment of pain during the waiting period before commencement of radiotherapy and during the radiotherapy period. Physicians and patients were recruited from 10 tertiary Class A hospitals across Shandong Province, China. Results: A total of 184 patients and 87 physicians were recruited to the study. During the waiting period, pain was reported by the physicians according to their experience to affect 26.0% of patients, which almost agreed with the patients' data (36.5%; 160 of 438). During the radiotherapy period, there was a significant difference in the reported prevalence of pain during the radiotherapy period between the physicians' data (23.0%) based on their experience and the patients' data (84.1%; 169 of 201 patients). The majority of physicians (98.9%; 86 of 87) agreed to the use opioids for pain management and 90.8% (79 of 87) were satisfied with the analgesic effect, but more than half of the patients who received pain treatment reported inadequate analgesia. Conclusion: There was a high incidence of cancer pain, but insufficient assessment, inadequate treatment and inadequate education about pain in both the waiting and radiotherapy periods.